Prevalencia de parasitosis intestinal, anemia y desnutrición en niños de un resguardo indígena Nasa, Cauca, Colombia, 2015 (2017)
ABSTRACT: To determine the prevalence of intestinal parasitosis, anemia and malnutrition among children of a Nasa indigenous reservation from Caldono in the Colombian department of Cauca, and their distribution according to clinical, sociodemographic and healthcareinfrastructure variables. Methodology: a crosssectional study with a primary source of information. Sixtytwo children were evaluated for intestinal parasites via stool analysis. Similarly, anthropometric measurements were used to assess nutritional status and determine the prevalence of various types of malnutrition. Likewise, the presence of anemia was determined by measuring hemoglobin levels. The group was described using summary measures for age and frequency measures for the other variables. Prevalence was calculated for intestinal parasites, anemia and malnutrition, and its association with independent variables was explored using hypothesis testing. The program SPSS 22.0 was used in this study. Results: The prevalence values were: 95.2% for intestinal parasites, 21% for anemia and 35.5% for chronic malnutrition. Although there was no statistical association with sociodemographic and health conditions in the study group, a high frequency of risk factors for intestinal parasites, anemia and malnutrition was found. These factors were: parents with low schooling levels, low availability of aqueducts and sewerage and high perceived morbidity. Conclusion: The evaluated indigenous community had a high prevalence of intestinal parasites, anemia and malnutrition. This has practical implications for the direction that healthcare programs targeting indigenous populations should take. Exploring the associations requires further studies with larger sample sizes which guarantee greater statistical power.